KARAKTERISTIK SIFAT FISIKO-KIMIA TEPUNG SUKUN (Artocarpus altilis) DENGAN VARIETAS TODDO’PULI - Masita, Sri; Wijaya, Mohammad; Fadilah, Ratnawaty (Universitas Negeri Makassar, 2017)
This study aims to determine the characteristics of physical properties and chemical properties of breadfruit flour Toddo'puli varieties. This research is experimental research, object in this research that is breadfruit flour which are made from varieties of Toddo'puli, with 3 times repeat so as to produce amount of unit trial counted 3 unit. Data of research obtained by way observation, documentation and experiment. files analysis techniques used are descriptive statistics. The results showed that the average value of yield obtained was 17.09%, viscosity 4,960 centipoise, moisture content 6,66%, amylose content 0,65%, amylopectin content 36,38%. While for organoleptic test of flour consist of color, smell and texture in a row get average value equal to 2,75%, 2,88%, 3,41%.